Math Problem Statement

Verify that 3 + 7 + 11 + ... + (4n - 1) = n(2n + 1) by using mathematical induction.

Solution

The problem asks us to verify by mathematical induction that:

3+7+11++(4n1)=n(2n+1)3 + 7 + 11 + \dots + (4n - 1) = n(2n + 1)

Step 1: Base Case (n = 1)

We first check if the formula holds true for n=1n = 1.

The left-hand side (LHS) for n=1n = 1 is: 3=4(1)13 = 4(1) - 1 So, the LHS is 3.

The right-hand side (RHS) for n=1n = 1 is: 1(2(1)+1)=1(2+1)=31(2(1) + 1) = 1(2 + 1) = 3 Thus, both the LHS and RHS are equal when n=1n = 1, so the base case holds.

Step 2: Inductive Hypothesis

Assume that the statement holds for some arbitrary n=kn = k, i.e., 3+7+11++(4k1)=k(2k+1)3 + 7 + 11 + \dots + (4k - 1) = k(2k + 1) This is our inductive hypothesis.

Step 3: Inductive Step (Prove for n=k+1n = k+1)

We need to show that the statement holds for n=k+1n = k + 1, i.e., 3+7+11++(4k1)+(4(k+1)1)=(k+1)(2(k+1)+1)3 + 7 + 11 + \dots + (4k - 1) + (4(k+1) - 1) = (k+1)(2(k+1) + 1) Using the inductive hypothesis, we know: 3+7+11++(4k1)=k(2k+1)3 + 7 + 11 + \dots + (4k - 1) = k(2k + 1) So, we add the next term (4(k+1)1)(4(k+1) - 1) to both sides: k(2k+1)+(4(k+1)1)k(2k + 1) + (4(k+1) - 1) Simplify 4(k+1)14(k+1) - 1: 4(k+1)1=4k+41=4k+34(k+1) - 1 = 4k + 4 - 1 = 4k + 3 Thus, the left-hand side becomes: k(2k+1)+(4k+3)k(2k + 1) + (4k + 3) Simplify the expression: k(2k+1)+4k+3=2k2+k+4k+3=2k2+5k+3k(2k + 1) + 4k + 3 = 2k^2 + k + 4k + 3 = 2k^2 + 5k + 3 Now, simplify the right-hand side for n=k+1n = k+1: (k+1)(2(k+1)+1)=(k+1)(2k+2+1)=(k+1)(2k+3)(k+1)(2(k+1) + 1) = (k+1)(2k + 2 + 1) = (k+1)(2k + 3) Expand this expression: (k+1)(2k+3)=(k+1)(2k+3)=2k2+3k+2k+3=2k2+5k+3(k+1)(2k + 3) = (k+1)(2k + 3) = 2k^2 + 3k + 2k + 3 = 2k^2 + 5k + 3 Both the left-hand side and right-hand side are equal, which completes the inductive step.

Conclusion:

Since the base case holds, and the inductive step has been proven, by mathematical induction, the given formula is true for all n1n \geq 1.


Do you need further details or have any questions? Here are five related questions:

  1. How does mathematical induction work in general?
  2. Why is it necessary to check the base case in induction?
  3. Can you provide another example of a series that can be proved using induction?
  4. What happens if the inductive step fails for some nn?
  5. How can this method of induction be applied to geometric progressions?

Tip: In mathematical induction, ensure your inductive hypothesis is clearly stated, as it forms the backbone of the inductive step.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Mathematical Induction
Arithmetic Series
Summation

Formulas

3 + 7 + 11 + ... + (4n - 1) = n(2n + 1)

Theorems

Principle of Mathematical Induction

Suitable Grade Level

Grade 11-12 (Advanced High School Mathematics)